From Darkness to Light Testimonies of Six Holocaust Survivors. - Diller, Ronald J. (Academic Studies Press, 2021)
A compilation of personal testimonies of six Holocaust survivors. Amid their immense pain and suffering, they overcame every hurdle they encountered and realized their dream to live in Israel. Their love for Israel and their creation of families embody children, grandchildren, and great-grandchildren nullified Hitler's aim to annihilate the Jews.